Pengembangan Desain Pembelajaran Matematika Materi SPLDV Dengan Teachmint Berbantuan Microsoft Math Solver - Donna Bella Kasiuhe; Victor R Sulangi; Anekke Pesik (Journal on Education, 2023)
This study aims to produce a mathematical learning design of two-variable linear equation system material with teachmint assisted by Microsoft Math Solver, which was carried out at SMK Kristen 2 Tomohon. This research uses the Generic EDR model by Mckenney and Reeves with the stages carried out, namely the analysis-exploration stage, the design-construction stage, the evaluation-reflection stage, the maturation stage of theoretical intervention-meaning, and the implementation stage. In the development of this learning design, there are three things that will be assessed, namely valid, practical and effective. The results showed that the average total validation score of the Teaching Module was 4.47 and the average total validation score of THB 4.55 with excellent categories that met the valid criteria. The results of the student response questionnaire showed an average total score of 4.31 which shows that the learning design is very practical. Then the percentage of completeness of the student learning outcomes test is 86.36, so this shows the design of the defender.